Digital crossroads telecommunications law and policy in the internet age - Nuechterlein, Jonathan E.; Weiser, Philip J. (The MIT Press, 2013)
In this book two experts on telecommunications policy offer a comprehensive and accessible analysis of the regulation of competition in the U.S. telecommunications industry.In this second edition, the authors have revised every section of every chapter to reflect the evolution in industry structure, technology, and regulatory strategy since 2005. The book features entirely new discussions of such topics as the explosive development of the mobile broadband ecosystem; incentive auctions and other recent spectrum policy initiatives; the FCC's net neutrality rules; the National Broadband Plan; the declining relevance of the traditional public switched telephone network; and the policy response to online video services and their potential to transform the way Americans watch television. Like its predecessor, this new edition of not only helps nonspecialists climb this field's formidable learning curve, but also makes substantive contributions to ongoing policy debates.